Collaboration & Innovation In Most Admired Knowledge Enterprise (MAKE): Case Studies Of Knowledge-Based Enterprise - Chen, Te Fu (Journal of Knowledge Management Practice, 2009)
In tomorrow's business environment, knowledge and how it is managed for competitive advantage will be the number one corporate priority. Firstly, this study explores sources of knowledge, managing knowledge, managing knowledge workers, Knowledge Management (KM) success factors. Secondly, the study reviews the implementation of intelligent business strategies, the award of most admired knowledge enterprise (MAKE) in knowledge-based enterprise, and how a firm used the infinite resource to creating and leading the knowledge enterprise.Thirdly, this research adopts the case study method to assess actual sources of knowledge and determinants of KM processes and how they can be leveraged to accumulate innovation capacity to the decision to implement a knowledge innovation in the context of the MAKE. The completed questionnaire, company reports/industry-specific newsletters and an in-depth interview created an established chain of evidence for each company. Fourthly, the study conducts three case studies of MAKE to find out the knowledge management, collaboration innovation and how it is managed for competitive advantage, and how a firm used the infinite resource to creating a platform and leading the knowledge enterprise.Finally, the study proposed the development trend of collaboration innovation, it emphasizes knowledge sharing should not only been limited in firm’s internal employees but also include firm’s external customers and cooperation partners, the situation also indicated the importance of “Collaboration” under knowledge economy. Furthermore, the study concludes the development trend of collaboration innovation via innovation through global collaboration: a new source of competitive advantage, build collaborative capabilities.
Keywords: Knowledge-based Enterprise; Collaboration; Innovation; MAKE